2011
DOI: 10.1088/0957-0233/22/7/075207
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a single-mode polymer optical fiber sensor and interrogator for large strain measurements

Abstract: A single-mode polymer optical fiber (POF) in a Mach–Zehnder interferometer configuration is validated for the measurement of tensile nominal elongation of the POF up to 10%. The single-mode POF sensors were unmounted and surface mounted on aluminum tensile coupons for strain measurements. The measured strains from the POF sensors were compared to extensometer measurements for validation. The phase response of the interferometer was measured with a 3 × 3 coupler interrogator. The coupler arrangement was configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In a sequential study [ 69 ], the nonlinear phase sensitivity was evaluated (3.1 × 10 6 rad.m −1 ) and the mechanical and photoelastic nonlinear coefficients were also calculated, being 11.4 and 16 respectively. In order to validate a SM-POF sensor and an interrogator for large strain measurements, this Mach-Zehnder interferometer was rearranged to allow an automated measurement of the phase shift [ 70 ]. A Mach-Zehnder interferometer based on the same approach was used to measure the phase shift induced by an ultrasonic wave emitted by a calibrated piezoelectric transducer on part of the optical fiber under test and immersed in water [ 71 ].…”
Section: Sensing Techniquesmentioning
confidence: 99%
“…In a sequential study [ 69 ], the nonlinear phase sensitivity was evaluated (3.1 × 10 6 rad.m −1 ) and the mechanical and photoelastic nonlinear coefficients were also calculated, being 11.4 and 16 respectively. In order to validate a SM-POF sensor and an interrogator for large strain measurements, this Mach-Zehnder interferometer was rearranged to allow an automated measurement of the phase shift [ 70 ]. A Mach-Zehnder interferometer based on the same approach was used to measure the phase shift induced by an ultrasonic wave emitted by a calibrated piezoelectric transducer on part of the optical fiber under test and immersed in water [ 71 ].…”
Section: Sensing Techniquesmentioning
confidence: 99%
“…It is worth mentioning that the large core size of both fibers provides tolerance to core misalignment in this connectorization method. However, for connectorizations between two single mode fibers with a core diameter of under 10 μm, this method is not applicable, since the POF core is not perfectly aligned in the geometric center of the ferrule, and thus the misalignment between cores of the POF and the SOF would result in much higher attenuation and degraded mode coupling 9 . Therefore, the connectors with high coupling losses could not be used for FBG inscription real-time monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…O. Abdi et al demonstrated an M–Z interferometer configuration using a single mode PMMA POF with a strain measurement of up to 10%. The phase response of the interferometer was measured with a 3 × 3 coupler interrogator and two photodetectors integrated with a data acquisition system [ 23 ]. Although PMMA POF can be used for M–Z interferometric sensors, the glass transition temperature and the elongation at break of the PMMA material are smaller than those for the PC material.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the large core size of both fibers provides tolerance to core misalignment in this connectorization method. However, for connectorization between two single-mode fibers with a core diameter of under 10 μm, this method is not applicable, since the POF core is normally not perfectly aligned in the geometric center of the ferrule, and thus the misalignment between cores of the POF and the SOF would result in much higher attenuation and degraded mode coupling [ 23 ]. Therefore, before going to the M–Z interferometric sensing part, a connection method by monitoring projecting images is demonstrated.…”
Section: Introductionmentioning
confidence: 99%